Mozambique Civil War and Farida Karodia’s A Shattering of Silence - Londhe, Sachin (Integrated Journal for Research in Arts and Humanities, 2023)
Mozambique civil war was fought between Mozambique’s ruling Marxist ‘Front for the Liberation of Mozambique’ (FRELIMO) and anti-communist insurgent forces of the ‘Mozambican National Resistance’ (RENAMO). Through the story of Faith, the novel reveals the reality of hundreds of thousands of children all over the world who are the victims of war, hunger, and political corruption. Being the sufferer of apartheid system, Farida Karodia has extensively written about the war, segregation during the apartheid, social and political situations in South Africa. ‘A Shattering of Silence’ deals with the history of colonialism and its brutal effects on the people of Africa.